Zimbabwe: Recent developments in agricultural research - Flaherty, Kathleen; Chipunza, Percy; Nyamukapa, Arthur (International Food Policy Research Institute, 2011)
Economic decline signifcantly constrained agricultural research and development (R&D) in Zimbabwe after 2002. The country relied on donor sources for much of its research funding in the 1990s, but by 2003 most donors had suspended their operations in Zimbabwe. Exacerbating matters, currency devaluations and hyperin ation during 2002-08 further eroded funding levels at agricultural R&D agencies and hence their ability to conduct viable research. This situation also led to high staff turnover, with many researchers moving to the private sector or to other countries. From a peak of almost 300 full-time equivalent (FTE) researchers in 1989, R&D capacity fell to a low of 139 FTEs in 2007, rebounding slightly to 148 FTEs in 2008 (Figure 1; Table 1).